THE FUNCTION OF IRONY AS A MEANS OF CREATING POLYSEMY AND MULTI-LAYERED TEXT (Web of Teachers: Inderscience Research, 2025)
The article examines the role of irony as one of the most important literary devices that contribute to the creation of multi-layered and polysemy of the text. Various functions of irony are analyzed: from comic to tragic, from the hidden author's mockery to deep philosophical reflections. Special attention is paid to the specificity of Chekhov's irony, its manifestations in the relationship between the characters, in the author's position and in the symbolic system of works A.P. Chekhov, demonstrating how irony helps to reveal hidden meanings, creating the effect of a double reading of the text.